The Economic Impact of Circling Disease in Sheep Flocks in Hama Governorate (Journal of Hama University, 2024)
This study aims to show the economic impact of circling disease caused by Listeria monocytogenes on sheep flocks in Hama Governorate, in order to arrive at an economic evaluation of the infection of circling disease in sheep flocks, using a model Livestock Productivity Efficiency Calculator (LPEC) analysis, of sheep flocks.Through the use of discriminatory media, and appropriate biochemical tests, in the detecting of Listeria monocytogenes, which causes infection of circling disease, the economic evaluation in this research was shown the circling disease affects the productivity of sheep flocks, if this disease is controlled, the productivity of one flock can increase by about 1866 US.$ per 100 sheep annually, compared to the presence of circling disease.
Keywords: Circling Disease; LPEC; Sheep Flocks; Hama Governorate